2011
DOI: 10.1525/jer.2011.6.4.41
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perspectives on Pediatric Genetic Research and Implications for Genotype-Driven Research Recruitment

Abstract: As genetic research is increasingly conducted in children, it is important to understand how parents make decisions about enrolling their children and what they think about receiving their children’s genetic research results. We conducted semi-structured phone interviews with 23 parents of children enrolled in genetic studies of autism or diabetes. Qualitative thematic analysis focused on two important components of genetic research and genotype-driven recruitment: participation in genetic research and return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 26 publications
(35 reference statements)
6
82
0
Order By: Relevance
“…10,11 The empirical evidence to understand parental attitudes toward the sharing of genomic research results derived from research with children has just begun to be explored. [12][13][14][15] There is also considerable debate about the extent to which family members should be informed of potentially relevant genomic information gathered in a pediatric context. 16,17 We used the rich resource of three Canadian consortia [18][19][20] that primarily study children to examine parental attitudes toward the return of genomic results.…”
mentioning
confidence: 99%
“…10,11 The empirical evidence to understand parental attitudes toward the sharing of genomic research results derived from research with children has just begun to be explored. [12][13][14][15] There is also considerable debate about the extent to which family members should be informed of potentially relevant genomic information gathered in a pediatric context. 16,17 We used the rich resource of three Canadian consortia [18][19][20] that primarily study children to examine parental attitudes toward the return of genomic results.…”
mentioning
confidence: 99%
“…42 Yet other commentators suggest that more advanced types of genetic research may be carried out without re-consent if similar genetic research was described in the original consent, as the goals, risks and benefits may be similar and therefore within the expectations of participants. 43 Similarly, DeCamp and Sugarman suggest that re-consent should occur before research into any topics considered 'controversial', such as 'violent behaviour', as it cannot be assumed that every participant would agree to be involved. 44 This obviously raises the question of what is controversial.…”
Section: Triggers For Re-consentmentioning
confidence: 99%
“…Here the ethical principle of autonomy (the basis of informed consent in contemporary research) is pitched against the 'right not to know' and the principle of non-maleficence (the precept to do no harm) 1 . This central tension in RbG research (also termed Genotype Driven Recruitment (GDR)) has been identified [2][3][4] in studies involving biobanks and other repositories that include participants with genotypic data collection, including disease and tissue-based biobanks [5][6][7] , population-based biobanks 5 and collections based on health records or direct to consumer testing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…While careful not to conflate the issues of return of clinically useful findings (incidental findings) with disclosure of genetic information through recruitment, these studies point to a range of cognate issues that bear consideration: the need to avoid participant anxiety if the genetic information -or re-contact itself -is unexpected 2,8 ; the possibility that even uncertain information may be important to participants 7 ; and the challenge that informational utility includes personal utility and personal meaning as well as clinical utility, especially where there is parental, familial or personal experience of disease [5][6][7]9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation